Sorption Equilibrium of Azo Dyes Direct Orange 26 and Reactive Blue 81 onto a Cheap Plant Sorbent - Tomczak, Elwira; Tosik, Paweł (Towarzystwo Chemii i Inżynierii Ekologicznej (TChiIE), 2014)
Azo dye-plant sorbent system was investigated in the paper. Direct Orange 26 and Reactive Blue 81 azo dyes were sourced from Boruta-Zachem Kolor Sp. z o.o. Mechanically and chemically modified rye straw was used as a “low-cost” biosorbent. During experiments, dye concentration changes in the solution and sorbent in time were measured at constant temperature until equilibrium was reached. Sorption equilibrium was described by 2-parameter (Freundlich, Langmuir) and 3-parameter (Redlich-Peterson and Radke-Prausnitz) equations widely used in adsorption studies. Characteristic coefficients of equations were determined and the proposed approximations of the results of experimental studies were evaluated statistically. Higher sorption capacity was obtained for Direct Orange 26 than for Reactive Blue 81.

W pracy prowadzono badania dla układu barwnik azowy - sorbent roślinny. Barwniki azowe Direct Orange 26 i Reactive Blue 81 pochodziły z Zakładu Boruta - Zachem Kolor Sp. z o.o. Jako biosorbenta użyto modyfikowanej fizycznie i chemicznie słomy żytniej, materiału taniego i łatwo dostępnego. Wykonano eksperymenty, kontrolując w czasie zmiany stężenia barwników w roztworze i sorbencie. Eksperymenty prowadzono w stałej temperaturze do ustalenia równowagi procesu. Opisu równowagi sorpcyjnej dokonano za pomocą równań dwu- i trójparametrowych szeroko stosowanych w adsorpcji. Wyznaczono charakterystyczne współczynniki równań i dokonano oceny statystycznej proponowanych aproksymacji wyników badań eksperymentalnych. Większą pojemność sorpcyjną uzyskano dla Direct Orange 26 niż dla Reactive Blue 81.
Równowaga Sorpcji Barwników Azowych Direct Orange 26 I Reactive Blue 81 Na Tanim Sorbencie Roślinnym
Keywords: azo dyes; rye straw; sorption isotherms; barwniki azowe; słoma żytnia; izotermy sorpcji